Gastrolinguistics Philosophical Wisdom Of Segas’ Produced In Tingkeban Traditional Ceremony As A Strengthening Of National Identity (Journal of Namibian Studies : History Politics Culture, 2023)
Saphir Whorf’s language raltivity theory stated that language covers the culture. This study analyzes the relationship between language and culture in sega’s production or rice produced from gastrolinguistics and philosophical wisdom perspectives. This is a qualitative study with data resources from the various of sega’s produced in tingkeban traditional ceremony. The unit analysis is gastrolinguistics, that is sega’s produced containing philosophical wisdom values. Researchers are the main instrument which is supported by research tools in the form of observation and interview guides and mobile phone to shoot documents and to record audio and video data. Techniques of collecting data are participant and non-participant observations. There are primary and secondary data. Primary data is obtained from the implementation of tingkeban ceremony, while secondary data was obtained from social media (instagram and whatsapp group of Indonesian Master of Ceremoy Association/PEPARI and Yogyakarta Pranatacara Association/PPY). Data validation are through persistent observation, peer discussion, repeated review, and source and method triangulations. The result shows that (1) the kinds and meanings of sega’s produced of philosophical wisdom are in tuned with the tingkeban ceremony, (2) the meaning of philosophical wisdom is based on gastrolinguistics’ typonimy and typology, (3) gastrolinguistics’ typonimy and typology are serve requirements for tingkeban traditional ceremony. Tingkeban is a traditional owned by Javanese people which has spread across the archipelago. Therefore, gastrolinguistic of tingkeban traditional ceremony can become the supporting capacity of national identity.